Fluminagrion gen. nov. for Acanthagrion taxaense Santos, 1965, from Brazil (Odonata: Coenagrionidae) - Anjos Dos Santos, Danielle (2013)
A new genus of Coenagrionidae, Fluminagrion, from Rio de Janeiro, Brazil is described, diagnosed, and illustrated, based on examination of the type series and additional specimens of Acanthagrion taxaense Santos, 1965, deposited in the collection of MNRJ/Brazil. This genus is characterized by: posterior lobe of prothorax trilobate, with medial lobe rounded and projected in both sexes; segment 3 of genital ligula C-shaped in lateral view, bifid in ectal view, ending in lobes directed laterally with apexes pyramidal in cross-section; male cercus entire and decumbent from proximal fourth, with brush-like setae at about half its length; female lacking mesepisternal fossa, S8 with vulvar spine. Um novo gênero de Coenagrionidae do Rio de Janeiro, Brasil, Fluminagrion é descrito, diagnosticado, e ilustrado, com base no exame da série-tipo e espécimes adicionais de Acanthagrion taxaense Santos, 1965, depositados na Coleção do MNRJ/Brasil. Este gênero é caracterizado por: lobo posterior do protórax trilobado, com lóbulo mediano arredondado e projetado em ambos os sexos; segmento 3 da lígula genital em forma de ‘C’ em vista lateral, bífido em vista ectal, terminado em lobos direcionados lateralmente com ápices piramidais na seção transversal; cercos do macho inteiros e descendentes a partir do quarto proximal, com um conjunto de setas em forma de pincel em cerca de metade de seu comprimento; fêmea sem fossa mesepisternal no mesepisterno, S8 com espinho vulvar.